2008
DOI: 10.1266/ggs.83.135
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the plastid and nuclear encoded CbbX proteins of Cyanidioschyzon merolae

Abstract: CbbX is believed to be a transcriptional regulator of the subunit genes (rbcL and rbcS) of RuBisCO (Ribulose 1,5-bisphosphate carboxylase/oxygenase) as well as possibly a molecular chaperon of RuBisCO subunit assembly. The unicellular red alga Cyanidioschyzon merolae strain 10D possesses two distinct cbbX genes; one is part of the plastid genome and the other is found in the cell nucleus, whereas the RuBisCO operon (rbcL-rbcS-cbbX) is located only on the plastid genome. We examined the role of CbbX proteins of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Similar to C . tobin , copies of cbbX were found in earlier studies of the cryptophyte Guillardia theta [ 84 ], where cbbX copies were found in the nucleomorph as well as chloroplast of this alga, followed by observations in the rhodophyte Cyanidioschyzon merolae [ 86 ] where cbbX was seen to occur in the nucleus as well as the chloroplast. Below we expand on preliminary observations that suggested that a broad phylogenetic occurrence of a chloroplast/nuclear cbb X coding duality exists in red lineage algae [ 87 ].…”
Section: Resultsmentioning
confidence: 88%
“…Similar to C . tobin , copies of cbbX were found in earlier studies of the cryptophyte Guillardia theta [ 84 ], where cbbX copies were found in the nucleomorph as well as chloroplast of this alga, followed by observations in the rhodophyte Cyanidioschyzon merolae [ 86 ] where cbbX was seen to occur in the nucleus as well as the chloroplast. Below we expand on preliminary observations that suggested that a broad phylogenetic occurrence of a chloroplast/nuclear cbb X coding duality exists in red lineage algae [ 87 ].…”
Section: Resultsmentioning
confidence: 88%
“…S1). These isoforms have been produced in E. coli previously, but were not tested for activase function (30). Following overexpression in E. coli, CmN was easily obtained at high purity by using a combination of affinity, anion-exchange, and size-exclusion chromatography ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A). Using primer extension mapping, a unique transcription initiation site was identified under dark and light conditions (Fujita et al, 2008b). Thus, transcription from the rbcL promoter was increased in response to the light.…”
Section: Transcription Activation Of the Rubisco Operon In Isolated Cmentioning
confidence: 99%
“…3A) mapped the binding site to the region from -59 to -30 (Fig. 3C), although the addition of 30-bp oligonucleotides seemed to cause a variation in the (Fujita et al, 2008b), translation initiation codon, and putative -10 box are indicated. Based on LTTR recognition sequence, three sequences (a-c) in the region from -59 to -30 are shown below the sequence.…”
Section: Sequence-specific Binding Of Ycf30 To the Promoter Region Ofmentioning
confidence: 99%